1985
DOI: 10.1038/315347a0
|View full text |Cite
|
Sign up to set email alerts
|

Size variation in chromosomes from independent cultured isolates of Plasmodium falciparum

Abstract: The complexity of the life cycle of the protozoan malaria parasite Plasmodium falciparum has hindered genetic analysis; even the number of chromosomes in P. falciparum is uncertain. The blood stages of rodent malaria parasites are haploid and hybridization with cloned complementary DNAs similarly suggests a haploid genome in P. falciparum blood stages (ref. 4 and our unpublished results). A novel approach to karyoptic and linkage analysis in P. falciparum has been provided recently by the technique of pulsed-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(57 citation statements)
references
References 14 publications
2
54
1
Order By: Relevance
“…Field isolates were collected from patients in Madang, Papua New Guinea, and cultured until schizont stage (1), and chromosome blocks were prepared as described (12). A twice-cloned Brazilian isolate, ItG2F6 (9), which had been in long-term culture, was recloned by limiting dilution (13) and by using a fluorescence-activated cell sorter.…”
Section: Methodsmentioning
confidence: 99%
“…Field isolates were collected from patients in Madang, Papua New Guinea, and cultured until schizont stage (1), and chromosome blocks were prepared as described (12). A twice-cloned Brazilian isolate, ItG2F6 (9), which had been in long-term culture, was recloned by limiting dilution (13) and by using a fluorescence-activated cell sorter.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been observed that the P.falciparum genome is highly polymorphic and subject to frequent DNA rearrangements (2,3,4,5). In other human parasites, such as Trypanosomes, DNA rearrangements are responsible for creating novel phenotypes and thus, are indicative of a mechanism generating antigenic variation (6).…”
Section: Introductionmentioning
confidence: 99%
“…They found that heterologous probes to the enzymes dihydrofolate reductase (mouse) and thymidylate kinase (yeast), hybridize to restriction digest fragments of DNA from various species of malaria parasites. Such an approach might open the way for sequence studies or chromosomal assignment (Kemp, Corcoran, Coppel, Stahl, Bianco, Brown & Anders, 1985) of the genes for the glycolytic enzymes which have long been used as genetic markers in Plasmodium (Walliker, 1983) as well as in other protozoan parasites.…”
Section: Discussionmentioning
confidence: 99%